Development of a reliable method to determine water content by headspace gas chromatography/mass spectrometry with the standard addition technique. Issue 11 (7th June 2015) - Inagaki, Shinsuke; Morii, Nahoko; Numata, Masahiko
<x xml:space="preserve">Abstract</x> A new and effective method for accurate water content determination using headspace gas chromatography/mass spectrometry (GC/MS) with the standard addition technique was developed.